2021
DOI: 10.1101/2021.05.11.21257016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative sensitivity evaluation for 122 CE-marked SARS-CoV-2 antigen rapid tests

Abstract: Objective Independent evaluation of the sensitivity of CE-marked SARS-CoV-2 antigen rapid diagnostic tests (Ag RDT) offered in Germany. Method The sensitivity of 122 Ag RDT was adressed using a common evaluation panel. Minimum sensitivity of 75% for panel members with CT<25 was used for differentiation of devices eligible for reimbursement in in the German healthcare system. Results The sensitivity of different SARS-CoV-2 Ag RDT varied over a wide range. The sensitivity limit of 75% for panel members wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…In a comparison of commercially available antigen POC tests, Scheiblauer et al [8] reported a sensitivity of 83.3% at Ct-values 25 or less for the antigen test used in this trial. We used this value as the presumed sensitivity for unvaccinated patients.…”
Section: Methodsmentioning
confidence: 70%
“…In a comparison of commercially available antigen POC tests, Scheiblauer et al [8] reported a sensitivity of 83.3% at Ct-values 25 or less for the antigen test used in this trial. We used this value as the presumed sensitivity for unvaccinated patients.…”
Section: Methodsmentioning
confidence: 70%
“…The timely initiation of antiviral therapy for SARS-CoV-2 will require the widespread availability of simple, affordable, and self-administered tests for the early diagnosis of SARS-CoV-2 infection. Current antigen tests fit well this demand with enough good sensitivity and specificity [47][48][49][50] . For the subset of persons at high risk for developing severe COVID-19 infection, short courses of antivirals as post-exposure prophylaxis might be considered.…”
Section: Prophylaxismentioning
confidence: 99%
“…In Europe, 950 CE-marked antigen tests (560 rapid) are currently on the market [12] . With continual increases in available tests, the number of validation studies has also increased but there are still only a small number of independent extensive comparative evaluations [13] , [14] , [15] . Also, data from external quality assessment (EQA) studies to evaluate the test performance amongst different users are required.…”
Section: Introductionmentioning
confidence: 99%